Quality Function Deployment (QFD) and Marketing: Towards Customer Satisfaction - Andrade, Jesús Alberto; Campo Redondo, María Susana (Revista de Ciencias Sociales, 2011)
The following paper illustrates how Quality Function Deployment (QFD) could be used to operacionalize the marketing concept. The relationship between marketing and satisfaction of the customer’s needs with the Quality Function Deployment criteria is examined. The QFD as management approach is described, giving special emphasis to the Voice of Consume’s (VOC) phase. The style of communication that results from the application of QFD is discussed. The advantages and limitations of the application of QFD are highlighted. Lastly, some conclusions are stated.